The Classification of Reading Text Questions in English Class at Tenth Grade of MAS Taman Raya Balingka - Yolanda Putri; Merry Prima Dewi; Veni Roza; Genta Sakti (Raudhatun Najah Publisher, 2022)
The research was triggered by several problems. First, Some sources book are not presenting HOTS model in several part of the book. Second, students have difficulty understanding questions in textbook. Third, The teacher does not provide teaching of Higher Order Thinking Skill (HOTS) while teaching process in order to maximize students higher order thinking skills. This research used quantitative research method. The subject was the questions in the textbook Bahasa Inggris X grade curriculum 2013 revisi 2017 written by Utami Widiati, Zuliati Rahmah, and Furaidah, which published Pusat Kurikulum dan Perbukuan, Balitbang, Kemendikbud. The researcher used items questions as the observation sheet of document for collecting and analyzing the data to find out the result of the research. This research found that the questions in the textbook did not include create of the cognitive process, based on bloom taxonomy revision. After doing analysis of the data, the researcher finds that the higher order thinking level only obtains 15 out of 74 items questions (20,25%). while the lower order thinking level 60 out of 74 items questions (79,20%). Results from this study show that the percentage of questions for each cognitive level is analyzing C4 (9,45%), evaluating C5 (6,75%), and creating C6(4,05%). This proportion does not meet the ideal proportion that supports the achievement of Basic Analysis Competence, the proportion questions that support are 30% for levels C1 and C2, 40% for levels C3 and C4, and 30% for levels C5 and C6.